Leadership Strategies in Vocational Education: Enhancing School Quality through Teacher Capacity Building - Anafika Amini; Fadlilah; Suci Fitriani (Journal of Educational Management Research, 2026)
This study aims to analyze school principals’ strategies for improving educational quality through the development of teaching personnel in vocational secondary education. A qualitative descriptive approach was employed, with data collected through observations, in-depth interviews, and documentation, and analyzed using data condensation, data display, and conclusion drawing techniques. The findings indicate that principals implement teacher development strategies through competency enhancement via training programs and the dissemination of training outcomes, reinforcement of discipline and continuous performance supervision, as well as the provision of support, recognition, and a collaborative work environment. These strategies contribute to increased teacher professionalism and improved learning quality. Nevertheless, challenges persist, including limited training quotas, inadequate learning support facilities, and restricted access to technology. To address these constraints, schools apply internal knowledge-sharing mechanisms, encourage teacher self-directed learning, and establish sustainable collaborations with industry partners and micro, small, and medium enterprises (MSMEs). The study underscores the critical role of strategic and effective school leadership in fostering teacher development as a key driver for enhancing the quality of vocational education and offers practical insights for educational leaders and policymakers in designing sustainable professional development initiatives.